2011
DOI: 10.1097/mao.0b013e318210b8fa
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Central and Peripheral Vestibular Pathology in Blast-Related Traumatic Brain Injury

Abstract: Vestibular function testing confirms a greater incidence of peripheral vestibular hypofunction in dizzy service members with blast-related TBI relative to those who are asymptomatic. Additionally, oculomotor abnormalities and/or nystagmus consistent with central involvement were present in 10 of the 24 study participants tested. The precise cause of these findings remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 44 publications
5
37
1
Order By: Relevance
“…In one report, static SVV was abnormal in only 11 percent of subjects [27], while in another study, SVV was abnormal in nearly all subjects (96%) [26]. In this latter study, however, it was not specified whether the abnormality was on the static or rotational test, and these are differentially sensitive to a peripheral versus a central locus of damage.…”
Section: Specific Effects Of Blast On Vestibular Functionmentioning
confidence: 81%
See 2 more Smart Citations
“…In one report, static SVV was abnormal in only 11 percent of subjects [27], while in another study, SVV was abnormal in nearly all subjects (96%) [26]. In this latter study, however, it was not specified whether the abnormality was on the static or rotational test, and these are differentially sensitive to a peripheral versus a central locus of damage.…”
Section: Specific Effects Of Blast On Vestibular Functionmentioning
confidence: 81%
“…In the latter study, twothirds of those having abnormal results showed patterns consistent with peripheral injury, whereas the results of the other third, or 8 percent overall, were consistent with central injury. Furthermore, abnormal nystagmus, mostly of central origin and equally distributed across etiology of trauma, was found during videonystagmography in 25 percent of patients in this study [27]. However, abnormal nystagmus was not present in another blast-exposed cohort [6].…”
Section: Specific Effects Of Blast On Vestibular Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…An important recommendation noted in this review (from Scherer et al [31] ) was that although some patients may appear to be asymptomatic, 30% of these asymptomatic patients had abnormal vestibular findings and nystagmus. Vestibular testing confirms a higher incidence of vestibular and oculomotor dysfunction in patients with blast-related TBI than in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the review involved reporting specifically on: (i) the description of nystagmus found in patients with TBI; (ii) the time to [29] 2008 [30] 2009 [31] 2011 [32] 2012 …”
Section: Outcomementioning
confidence: 99%